Enantiodromia : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Adamson, Richard Douglas (Massey University, 2021)
This exegesis explores the trajectory of my artistic practice between 2020-2021. It begins with a prologue discussing a childhood memory that resurfaced on multiple occasions throughout my MFA. Two further areas of interest from my personal history – the concept of enantiodromia and the Zen Buddhist tenet of “nothingness” – are also offered as the main threads that run through my entire thesis project. I then discuss a group of drawings I brought with me into the MFA which became the visual foundation on which my current work was constructed. My art historical background from late Gothic through to Surrealism and other relevant artist models I discovered during the MFA such as Josef Albers and Donald Judd, work to contextualise my arts practice and anchor it in both historical artistic precedent and modern art theory. My methodology is centred around the notion of iteration, and I suggest my attempts at manipulation of the display environment I hang my paintings in is yet another step in the iterative journey of searching. This searching is then tied in with the repetition of the motif in my imagery. I also include a discussion of my intentions for the final display of my work at the end of the MFA and how it may be the final stage of the MFA but it is also a stepping off from this chapter and onto the next, suggesting further areas of development and exploration.
Keywords: Painting; installation; immersive experience; dream-nightmare; Carl Jung; dream interpretation; archetype; enantiodromia; Zen Buddhism; "nothingness"; 'scapes; motif; documentation; iteration; tension of opposites; paradox; closed loop; light; shadow; time of day; 360602 Fine arts